CITREX 401 products flourish innovation culture - Rozaimi, Abu Samah (2020)
The 10th edition of Creation, Innovation, Technology & Research Exposition (CITREx) 2020 saw Universiti Malaysia Pahang (UMP) as the platform for encouraging and nurturing the innovation culture among the researchers including academicians and students not only from UMP but also from the Malaysian Technological University Network (MTUN), Kolej Poly-Tech MARA, Advanced Technology Training Center (ADTEC) and other higher education institutions (HEI) across the country.